MITIGASI BENCANA TSUNAMI BERBASIS EKOSISTEM MANGROVE DI DESA NANIA KOTA AMBON - Juglans Howard Pietersz; Jan Willem Hatulesila; Gun Mardiatmoko; Simson Liubana (Universitas Pattimura, 2026)
Mangrove forests serve as natural green barriers that play a crucial role in disaster mitigation. However, their existence as ecological buffers for both terrestrial and marine environments is often overlooked due to development pressures. Nania Village represents an example of urban expansion that directly intersects with mangrove areas in the Inner Ambon Bay. Preliminary assessments indicate that the community is largely unaware of their daily interactions that may contribute to the degradation of the local mangrove ecosystem. This community engagement activity was designed to provide education to the residents of Nania, fostering greater awareness of the importance of mangrove forests as a key component of disaster mitigation. The program was carried out through public outreach sessions, collective clean-up activities within the mangrove area, and mangrove planting actions. As a result, the initiative successfully strengthened community awareness and commitment to protecting and conserving the surrounding mangrove forests, thereby reducing the potential risks of natural disasters, particularly tsunamis.